2022
DOI: 10.3390/ijerph192214972
|View full text |Cite
|
Sign up to set email alerts
|

Application of Two-Eyed Seeing in Adolescent Mental Health to Bridge Design Thinking and Indigenous Collective Storytelling

Abstract: Background: eMental health apps are increasingly being considered for use in health care with growing recognition of the importance of considering end-user preferences in their design and implementation. The key to the success of using apps with Indigenous youth is tailoring the design and content to include Indigenous perspectives. In this study we used a Two-Eyed Seeing perspective to integrate Indigenous and human computer interaction methodologies to identify end-user preferences for a tablet-based mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Statement Acknowledging Indigenous Knowledge during Analysis. Three (n = 32; 7%) articles (Hall et al, 2015;Jaworsky, 2023;Sam et al, 2022;Wright et al, 2019c) of the 32 articles included a statement acknowledging Indigenous Knowledge during research analysis. In a study by Hall et al (2015), the research team identified that participant stories would be treated as Indigenous Knowledge including complex teachings, humorous additions, historical happenings, and/or sacred tellings depending on the intent of the shared story.…”
Section: Jacklinementioning
confidence: 99%
See 1 more Smart Citation
“…Statement Acknowledging Indigenous Knowledge during Analysis. Three (n = 32; 7%) articles (Hall et al, 2015;Jaworsky, 2023;Sam et al, 2022;Wright et al, 2019c) of the 32 articles included a statement acknowledging Indigenous Knowledge during research analysis. In a study by Hall et al (2015), the research team identified that participant stories would be treated as Indigenous Knowledge including complex teachings, humorous additions, historical happenings, and/or sacred tellings depending on the intent of the shared story.…”
Section: Jacklinementioning
confidence: 99%
“…Nine articles (Bruner et al, 2019;Carter et al, 2017;Hall et al, 2015;Hatala et al, 2020;Jacklin et al, 2020;Martin et al, 2018;Stelkia et al, 2021;Vorobyova et al, 2022;Wright et al, 2019c) used two of the strategies and three articles (Latimer et al, 2020;Marsh et al, 2015;Rowan et al, 2015) used three strategies to involve Indigenous community members. Overall, all but five article (Jaworsky, 2023;Pilarinos et al, 2023;Sam et al, 2022;Shrivastava et al, 2020;Sylliboy, 2021) used a strategy to involve Indigenous community members during data analysis.…”
Section: Themes and Sub-themesmentioning
confidence: 99%